1972
DOI: 10.1113/jphysiol.1972.sp009769
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vasodilator responses to hypoxia before and after aminophylline

Abstract: SUMMARY1. In previous studies adenosine has been postulated to be the mediator in coronary blood flow regulation and aminophylline was found to inhibit the coronary vasodilator action of adenosine. The present study was performed to determine whether aminophylline inhibits coronary vasodilatation induced by hypoxia.2. Coronary and systemic haemodynamic and metabolic effects of hypoxia were studied in anaesthetized dogs before and after aminophylline. Aminophylline did not influence coronary vasodilatation indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…This would then induce dilatation of the coronary resistance vessels. Nevertheless, doubts concerning this hypothesis have been raised by several authors (Bittar & Pauly, 1971;Afonso, Ansfield, Berndt & Rowe, 1972) who showed that the administration of aminophylline left reactive hyperaemia responses unchanged but blocked the responses to adenosine. Moreover, it has been shown that adenosine 5'-triphosphate (ATP), adenosine 5'-pyrophosphate (ADP) and adenosine 5'-phosphate (AMP) are more potent coronary vasodilators than adenosine (Moir & Downs, 1972; ATP has been found in the perfusate of hypoxic guinea-pig heart (Paddle & Burnstock, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…This would then induce dilatation of the coronary resistance vessels. Nevertheless, doubts concerning this hypothesis have been raised by several authors (Bittar & Pauly, 1971;Afonso, Ansfield, Berndt & Rowe, 1972) who showed that the administration of aminophylline left reactive hyperaemia responses unchanged but blocked the responses to adenosine. Moreover, it has been shown that adenosine 5'-triphosphate (ATP), adenosine 5'-pyrophosphate (ADP) and adenosine 5'-phosphate (AMP) are more potent coronary vasodilators than adenosine (Moir & Downs, 1972; ATP has been found in the perfusate of hypoxic guinea-pig heart (Paddle & Burnstock, 1974).…”
Section: Resultsmentioning
confidence: 99%
“…Berne (1963) hypothesized that adenosine was the physiologic regulator of blood flow during reactive hyperemia, and this hypothesis dominated the field for the next decade, although clear supporting evidence was lacking (see Nees et al, 1985;Zucchi et al, 1989). For example, an adenosine receptor antagonist, theophylline, failed to block reactive hyperemia, although it blocked the vasodilator actions of exogenously applied adenosine (Afonso et al, 1972;Bünger et al, 1975). Intracoronary adenosine and ATP increased coronary blood flow, but reactive hyperemia in the dog heart after occlusion was not blocked by the adenosine receptor antagonist aminophylline (Eikens and Wilcken, 1973a,b;Giles and Wilcken, 1977;Clemens et al, 1985a).…”
Section: E Coronary Vesselsmentioning
confidence: 99%
“…The influence of oxygen tension on vascular resistance is a well-known phenomenon (Markwalder & Starling, 1913;Green & Wegria, 1941;Berne et al 1957;Carrier, Walker & Guyton, 1964;Daugherty, Scott, Dabney & Haddy, 1967;Detar & Bohr, 1968;Afonso, Ansfield, Berndt & Rowe, 1972;Duvelleroy et al 1973;Gellai, Norton & Detar, 1973). The possible roles of oxygen tension as the underlying mechanisms ofautoregulation and metabolic vasodilation have also been discussed (Belloni, 1979).…”
Section: Theoretical Backgroundmentioning
confidence: 99%